Issue dedicated to late Dr F. P. Amerasinghe - University of Peradeniya (Sri Lanka Journals Online, 2008)
This issue of the Ceylon Journal of Science (Bio. Sci.) is dedicated to the memory of Dr. F.P Amerasinghe who passed away on 7th June 2005 at the age of 57. At the time of his demise he was attached to the International Water Management Institute (IWMI), CGIAR Research Center in Sri Lanka, as the theme leader for the Water, Health and Environment division. Prior to joining IWMI in 2001, Dr. Amerasinghe was attached to the University of Peradeniya, where he spent the major part of his life as an outstanding academic and a researcher.